Narrative and Communication Analysis of Advertising Placement in the Short Video Era: Take the Blogger "Art Cauliflower" as an Example - Wang, Yucheng (International Journal of Social Sciences and Public Administration, 2024)
In today’s era, short videos appear more and more frequently in people’s life. The focus of the development of the advertising industry is gradually getting closer to short video, and short video platforms are gradually replacing traditional media such as newspapers and TV as a new way of communication. Therefore, in order to achieve outstanding communication effect, it is necessary to change the content and form of the video to make it more close to the audience’s preferences. In order to better develop the short video advertising, the article will take the short video blogger "Art Cauliflower" as an example to analyze the short video advertising from two aspects of narrative and communication, and put forward relevant suggestions for the current short video.